2016
DOI: 10.1111/vsu.12601
|View full text |Cite
|
Sign up to set email alerts
|

Total laparoscopic gastropexy using 1 simple continuous barbed suture line in 63 dogs

Abstract: Total laparoscopic barbed gastropexy using a single, simple continuous, barbed suture line in dogs is safe and results in an intact gastropexy long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 27 publications
8
53
1
Order By: Relevance
“…2 All previously described laparoscopic gastropexy techniques have been performed with an incision in the seromuscular layer of the stomach and the transversus abdominis muscle with either laparoscopic Metzenbaum scissors or harmonic scalpel. 4,5,10,13,14 In the present study, no incision was performed before gastropexy. Previous studies reported a laparoscopic-assisted gastropexy technique that used monopolar electrosurgery to scarify the peritoneum at the intended gastropexy sites on the body wall and stomach, instead of making an incision through the seromuscular layer of the stomach and the transversus abdominis muscle.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…2 All previously described laparoscopic gastropexy techniques have been performed with an incision in the seromuscular layer of the stomach and the transversus abdominis muscle with either laparoscopic Metzenbaum scissors or harmonic scalpel. 4,5,10,13,14 In the present study, no incision was performed before gastropexy. Previous studies reported a laparoscopic-assisted gastropexy technique that used monopolar electrosurgery to scarify the peritoneum at the intended gastropexy sites on the body wall and stomach, instead of making an incision through the seromuscular layer of the stomach and the transversus abdominis muscle.…”
Section: Discussionmentioning
confidence: 92%
“…1,3,6,7 Total laparoscopic gastropexies have been gaining popularity. [4][5][6][7][8][9][10][11][12][13][14] Total laparoscopic gastropexy has been demonstrated to be superior to both open-and laparoscopicassisted methods in terms of decreased postoperative pain. 4,5,10,13 Prophylactic gastropexy can be performed at the time of a routine surgery such as ovariectomy, castration, cryptorchidectomy, exploratory laparotomy for foreign body obstructions, and visceral organ biopsies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The successful use of knotless barbed suture has been reported in the veterinary literature for use in laparoscopic gastropexy, enterotomy, gastrotomy, and intradermal wound closure. [17][18][19][20][21][22][23][24][25] Quill ™ suture was introduced initially as a barbed monofilament suture made from polypropylene, nylon, or glycolic acid derivatives. The suture has a curved, diamond-pointed needle on each end of the strand.…”
Section: Discussionmentioning
confidence: 99%